THE ROLE OF TEACHERS IN THE IMPLEMENTATION OF THE T3Q PROGRAM FOR INTERNALIZING CHARACTER VALUES - Nur Apriyani; A Marjuni; Muhammad Nur Akbar Rasyid; Baharuddin Baharuddin; Mahyuddin Mahyuddin (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Character education in early childhood is crucial for the development of personality and morals in the subsequent stages of education. However, it is often not systematically integrated into the learning process. The T3Q Program (Tahsin, Tahfidz, and Tadabbur Qur'an) at Athirah Islamic Kindergarten Bukit Baruga Makassar provides a strategic platform for internalizing Qur'an-based values from an early age, which supports the development of a strong character in children. This study aims to analyze the strategies and roles of teachers in instilling character values in children, as well as to identify the factors that support and hinder this process. The approach used in this study is qualitative phenomenology, where data was collected from the principal, T3Q teachers, classroom teachers, and students through observations, interviews, and document studies. The collected data were then analyzed through stages of data reduction, presentation, and conclusion drawing. The results of the study show that teachers play a crucial role in designing value-based learning, being moral role models, facilitating habit formation, managing emotions, interpreting Qur'anic values, evaluating the development of children's character, and linking the school with the family. The main supporting factors include the school’s commitment, program consistency, the teacher's role model, the Islamic culture present in the school, and parental involvement. However, there are also hindering factors such as variations in children's readiness and limited instructional time. The study concludes that consistent integration of character education, supported by the role model of teachers and reinforced through programs like IHF, can effectively instill character values such as honesty, discipline, responsibility, and care. Close collaboration between school and family is crucial for strengthening the development of children's character. This study emphasizes the role of the T3Q Program in Qur'anic-based character education, as well as the important role of teachers in exemplifying these values and shaping children's character. Future research could explore the long-term impact of these programs and the role of parents in supporting the internalization of character values in children.